2008
DOI: 10.1038/nm1701
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive in vivo imaging of pancreatic islet cell biology

Abstract: Advanced imaging techniques have become a valuable tool in the study of complex biological processes at the cellular level in biomedical research. Here, we introduce a new technical platform for noninvasive in vivo fluorescence imaging of pancreatic islets using the anterior chamber of the eye as a natural body window. Islets transplanted into the mouse eye engrafted on the iris, became vascularized, retained cellular composition, responded to stimulation and reverted diabetes. Laserscanning microscopy allowed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
331
0
6

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 242 publications
(347 citation statements)
references
References 29 publications
10
331
0
6
Order By: Relevance
“…Techniques used to study the biology of islet of Langerhans in situ, using LSM, were rather invasive and did not allow repetitive imaging at all or only over a limited time period 14,15 . We showed that, after transplantation to the anterior chamber of the eye, isolated islets readily engrafted 13 . Diabetic mice could be rendered normoglycemic by transplanting islets of Langerhans to the anterior chamber of their eye, and these mice showed identical responses to glucose tolerance tests compared to control mice.…”
Section: High-resolution In Vivo Imaging In the Anterior Chamber Of Tmentioning
confidence: 97%
See 2 more Smart Citations
“…Techniques used to study the biology of islet of Langerhans in situ, using LSM, were rather invasive and did not allow repetitive imaging at all or only over a limited time period 14,15 . We showed that, after transplantation to the anterior chamber of the eye, isolated islets readily engrafted 13 . Diabetic mice could be rendered normoglycemic by transplanting islets of Langerhans to the anterior chamber of their eye, and these mice showed identical responses to glucose tolerance tests compared to control mice.…”
Section: High-resolution In Vivo Imaging In the Anterior Chamber Of Tmentioning
confidence: 97%
“…We have recently used the protocol described in this article to transplant isolated pancreatic islets of Langerhans into the anterior chamber of the eye 13 . Studies on vascularized and innervated islets of Langerhans are necessary to understand the mechanisms leading to hormone secretion in health and in diseases such as type 1 and type 2 diabetes.…”
Section: High-resolution In Vivo Imaging In the Anterior Chamber Of Tmentioning
confidence: 99%
See 1 more Smart Citation
“…Essentially, with xfOCM the islets are studied in their natural environment, and disease evolution and islet destiny can be evaluated. This is in contrast to the anterior eye chamber imaging platform [12] that is limited to the study of the engraftment process and graft function in an immunologically privileged engraftment site. Although lacking molecular specificity, xfOCM is potentially able to measure islets in any site accessible to the microscope, provided the islets contrast with the surrounding tissue.…”
Section: Discussionmentioning
confidence: 99%
“…In recent work [12] islets have been transplanted into the mouse eye. Engrafted on the iris they could be repeatedly imaged using the eye as a natural body window.…”
mentioning
confidence: 99%